Penerapan SMK3 Berdasarkan OHSAS 18001: 2007 di PT. APF Tbk - Herry Koesyanto; Hadi Setyo Subiyono (Dian Nuswantoro Semarang, 2017)
Based on data from Jamsostek, indicated that the number of occupational accidents that occurred in Indonesia was still very high, in 2013 had occurred as many as 103 285 cases of occupational accidents, based on the data is that the accident happened experienced an average increase of 1.76% annually. the accident number at PT. APF Tbk. Kendal in 2014 was 17 cases. The purpose of this research was to describe the application of SMK3 based on OHSAS 18001: 2007 in PT. Asia Paciic Fibers Tbk. Kendal. This research used descriptive research and design. Test the validity of the data using triangulation techniques. Results from this study PT. APF Tbk. has implemented the requirements 144 points of the overall 150 points SMK3 application based on OHSAS 18001: 2007, while the number of points that have not it as much as 5 points requirements and points requirements are not met by 1 pointKeywords: SMK3, OHSAS 18001, Management